What Makes Diets Political? Moral Foundations and the Left-Wing-Vegan Connection. - Grünhage, Thomas; Reuter, Martin (Social Justice Research, 2021)
Though meat-consumption is known to be a key factor in environmental damage, veganism and vegetarianism are still perceived to be left-wing-phenomena, ironically not penetrating to those who hold ideologies of conservation. Logical contradictions and historical counter-examples cast doubt on a substantive connection between political orientation and meat-eating. Instead, common psychological factors may predispose people toward both: left vs. right-wing political orientation and self-restrictive vs. omnivore eating preferences. Moral foundations have been shown to explain why even seemingly contradictory issue stances are brought forward in the context of the same ideological or political orientation. Here, we expand on these findings by showing the moral foundations to connect political orientation and vegan and vegetarian eating preferences as well as specific strategies of meat-eating justification in a large German sample. Specifically, the binding foundations authority and purity as well as avoidance tendencies are shown to differentially interact with meat-eating across the political spectrum with stronger effects for left-wing adherents and centrists than for the right-wing. Mediation analyses reveal that substantive parts of the association between political orientation and self-restriction in eating are attributable to differences in the moral makeup of left- and right-wing adherents. Connecting our results to prior work on the explanatory power of moral foundations for the political polarization of environmentalism, we discuss how our results may inform inter-ideologically appealing communications of reducing meat consumption, which is a worthwhile and necessary goal for mitigating climate change.